SALNAMELERE GÖRE TRABZON VİLAYETİNDE DİNİ VE SOSYAL YAPI - TOPAL, İBRAHİM (Fırat Üniveristesi, 2012)
XV. yüzyıla sancak merkezi olan Trabzon, Osmanlı vilayet sistemi içerisinde önemli bir vilayet merkezi olmuş, bünyesinde çeşitli inanç ve kültürleri de birlikte yaşatmıştır. Bu cümleden olarak Müslümanların dini ve sosyal kurumlarının yanı sıra her dönem gayrimüslimlere ait inanç ve kültürel değerleri yaşatan kurumlar da salnamelerde yerini almıştır. Bu verilerden hareketle merkezden başlayarak Trabzon'da yaşayan Müslim ve gayrimüslim nüfusu dini gruplar halinde değerlendirilmiştir.Anahtar Kelimeler:Trabzon, Müslüman, Gayrimüslim, Sosyal Kurumlar, Dini Kurumlar, Nüfus.

Trabzon, which was flag center in 15th century, was an important city center inside the province system of Ottoman Empire and a lot of religions and cultures were living in Trabzon. Therefore, besides Muslims? social and religious foundations, in annuals, there were lots of religious and social foundations which were belongs to non-Muslims. In the light of these information, starting with the center, Muslims and non-Muslims, populations which were living in Trabzon, were evaluated according to their religious groups.Key Words: Trabzon, Muslim, non-Muslim, Social Foundation, Religious Foundation, Population.
Religious and social structurein Trabzon provincein respect of yearbooks
Keywords: Din; Tarih